Novel hydroxyapatite nanorods improve anti-caries efficacy of enamel infiltrants. Issue 6 (June 2016) - Andrade Neto, D.M.; Carvalho, E.V.; Rodrigues, E.A.; Feitosa, V.P.; Sauro, S.; Mele, G.; Carbone, L.; Mazzetto, S.E.; Rodrigues, L.K.; Fechine, P.B.A.
Graphical abstract: Highlights: The presence of more crystalline hydroxyapatite nanorods increases the degree of conversion of enamel infiltrants. Incorporation of hydroxyapatite nanorods in resin infiltrantes induced resistance of surrounding and underlying enamel to recurrent acidic challenges. Abstract: Objectives: Enamel resin infiltrants are biomaterials able to treat enamel caries at early stages. Nevertheless, they cannot prevent further demineralization of mineral-depleted enamel. Therefore, the aim of this work was to synthesize and incorporate specific hydroxyapatite nanoparticles (HAps) into the resin infiltrant to overcome this issue. Methods: HAps were prepared using a hydrothermal method (0 h, 2 h and 5 h). The crystallinity, crystallite size and morphology of the nanoparticles were characterized through XRD, FT-IR and TEM. HAps were then incorporated (10 wt%) into a light-curing co-monomer resin blend (control) to create different resin-based enamel infiltrants (HAp-0 h, HAp-2 h and HAp-5 h), whose degree of conversion (DC) was assessed by FT-IR. Enamel caries lesions were first artificially created in extracted human molars and infiltrated using the tested resin infiltrants. Specimens were submitted to pH-cycling to simulate recurrent caries. Knoop microhardness of resin-infiltrated underlying and surrounding enamel was analyzed before and after pH challenge. Results: Whilst HAp-0 h resulted amorphous, HAp-2 h and HAp-5 h presented nanorod morphology and higher crystallinity. Resin infiltration doped with HAp-2 h and HAp-5 h caused higher enamel resistance against demineralization compared to control HAp-free and HAp-0 h infiltration. The inclusion of more crystalline HAp nanorods (HAp-2 h and HAp-5 h) increased significantly ( p < 0.05) the DC. Significance: Incorporation of more crystalline HAp nanorods into enamel resin infiltrants may be a feasible method to improve the overall performance in the prevention of recurrent demineralization (e.g. caries lesion) in resin-infiltrated enamel.